2008
DOI: 10.1016/j.jcrs.2008.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Influence of preoperative keratometry on refractive results after laser-assisted subepithelial keratectomy to correct myopia

Abstract: Preoperative corneal curvature did not seem to influence the spherical refractive outcomes after myopic LASEK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Another study of the effect of keratometry on refractive outcome was carried out by de Benito-Llopis et al [ 20 ] in LASEK cases on 1180 eyes and found that there is a weak positive correlation between preoperative keratometry and postoperative SE, mostly in the subgroup with steeper corneas and when the preoperative refractive error was higher. Yet they did not find a tendency toward undercorrection in flatter corneas, as some studies of LASIK have concluded.…”
Section: Discussionmentioning
confidence: 99%
“…Another study of the effect of keratometry on refractive outcome was carried out by de Benito-Llopis et al [ 20 ] in LASEK cases on 1180 eyes and found that there is a weak positive correlation between preoperative keratometry and postoperative SE, mostly in the subgroup with steeper corneas and when the preoperative refractive error was higher. Yet they did not find a tendency toward undercorrection in flatter corneas, as some studies of LASIK have concluded.…”
Section: Discussionmentioning
confidence: 99%
“…Even though small-incision lenticule extraction (SMILE) is a safe, efficient, and predictable surgical method for correction of myopia, the predictability of the technique as well as laser in situ keratomileusis (LASIK) and surface ablation is disputed, especially in eyes with high degrees of myopia or hyperopia [1][2][3][4][5][6][7][8][9]. To date, a few studies have evaluated the effect of preoperative keratometry on visual outcomes after LASIK or surface ablation and predictors of SMILE outcomes [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed no relationship between preoperative corneal curvature and postoperative predictability after myopic laser-assisted subepithelial keratectomy (LASEK) [ 14 ]; however, when treating preoperative higher myopia in steeper corneas, a weak tendency existed toward overcorrection [ 12 ]. In previous studies evaluating the effect of preoperative keratometry (K) on visual outcomes after LASIK for myopia, eyes with flatter corneas tended to have greater undercorrection than eyes with similar myopia and steeper corneas, and undercorrection and loss of best spectacle-corrected visual acuity following hyperopic LASIK in eyes with steep corneas [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] To date, a few studies have evaluated the effect of preoperative keratometry on visual outcomes after LASIK or surface ablation and predictors of SMILE outcomes. [10][11][12][13] Previous studies showed no relationship between preoperative corneal curvature and postoperative predictability after myopic laser-assisted subepithelial keratectomy (LASEK); [14] however, when treating preoperative higher myopia in steeper corneas, a weak tendency existed toward overcorrection. [12] In previous studies evaluating the effect of preoperative keratometry (K) on visual outcomes after LASIK for myopia, eyes with atter corneas tended to have greater undercorrection than eyes with similar myopia and steeper corneas, and undercorrection and loss of best spectacle-corrected visual acuity following hyperopic LASIK in eyes with steep corneas.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Previous studies showed no relationship between preoperative corneal curvature and postoperative predictability after myopic laser-assisted subepithelial keratectomy (LASEK); [14] however, when treating preoperative higher myopia in steeper corneas, a weak tendency existed toward overcorrection. [12] In previous studies evaluating the effect of preoperative keratometry (K) on visual outcomes after LASIK for myopia, eyes with atter corneas tended to have greater undercorrection than eyes with similar myopia and steeper corneas, and undercorrection and loss of best spectacle-corrected visual acuity following hyperopic LASIK in eyes with steep corneas. [10,11] Besides, moderately myopic eyes with atter corneas preoperatively show better visual prognosis following LASIK compared with steeper corneas.…”
Section: Introductionmentioning
confidence: 99%